PENGEMBANGAN LKPD BERBASIS PENDEKATAN SAINTIFIK - rati, Nursidrati (JPSL : Jurnal Pendidikan, Sosial dan Lingkungan, 2024)
This research is development research which aims to produce interactive media based on guided discovery learning for class VII students. The validation test results show that the student worksheet is valid with a score of 82%. On the other hand, product trials with students showed that the media was practical with a score of 84.4%. Therefore, the scientific approach-based student worksheets developed meet the quality aspects, namely valid and practical. Research also shows that media can facilitate and motivate student learning.